NEUROCYSTICERCOSIS IN SOLID ORGAN TRANSPLANTATION PATIENTS - Wiwanitkit, Viroj (Malang Neurology Journal, 2019)
The neurocysticercosis is an important neurological infection. It can be seen in several tropical countries. The neurocysticercosis can affect both healthy people and patients. The organ transplant patient can also get neurocysticercosis. Similar to general case, the neurocysticercosis in organ transplant patients might present with neurological presentation. The practitioner should include neurocysticercosis in differential diagnosis of unexplained neurological episode in any patients with solid organ transplantation.